Challenges in Marriage Document Verification and Their Implications for Marriage Validity: An Empirical Study of KUA Tambaksari, Surabaya - Syaddad Azizi; Saiful Ibnu Hamzah; Salman Al Farisi (Universitas Islam Negeri Raden Intan Lampung, 2025)
The circulation of forged marriage books demonstrates the weakness of the marriage administration verification system, which has resulted in legal uncertainty and the loss of protection of the civil rights of married couples and children. This study aims to analyze the problematics of marriage document verification at the Office of Religious Affairs (Kantor Urusan Agama/KUA) of Tambaksari District, Surabaya, as well as its legal implications for the validity of marriage and the protection of citizens’ rights. This study employs qualitative research with normative juridical and empirical approaches. Data were obtained through participant observation during internship activities, semi-structured interviews with KUA employees, and documentation studies concerning marriage-administration archives. Data analysis was conducted using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing. The findings demonstrate that the implementation of document verification at KUA Tambaksari has not yet operated optimally due to the absence of standardized operational procedures, weak archival management, verification processes that continue to depend upon subjective visual examination, and the low level of coordination with law enforcement authorities. These conditions create uncertainty regarding the legal status of marriage and burden married couples with the obligation to pursue isbat nikah proceedings in order to obtain state recognition. This study recommends strengthening integrated digital-based verification policies, formulating SOPs for handling problematic documents, and improving interinstitutional coordination in order to ensure legal certainty and the protection of citizens’ civil rights.